A comparative study of songs and singing styles of Teresa Teng and Faye Wong / Chai Zilong - Chai, Zilong (2018)
This research examines into the development of Chinese popular singing in the 90s by focusing on a case comparing Faye Wong and her cover version of Teresa Teng’s song in her album Decadent Sounds of Faye and the original Teresa Teng’s singing style. Most literatures about Chinese popular artists and their singing styles lack analysis that look into its stylistic development in relation to the artist’s personae and cultural identity. Therefore, this research discusses the precedent artist Teresa Teng’s voice type and style in the 80s, subsequently followed by Faye Wong’s cover version, showing a development of styles where the latter moved towards the West. Analyzing both artists’ rendition of the same selected songs reveals how Faye Wong’s cover version in the 90s is being more westernised where the findings present the case study of C-pop and its stylistic development. Qualitative methods include virtual fieldwork and analysis were based on Tagg’s model (1982). The outcome presents transcribed excerpts of the two singing styles that depicts how Chinese pop singing gradually moved away from its folk-like identity to a more glocalized output, and a discussion of Faye Wong’s positioning ‘song personality’ and ‘star personality’ as in the concept of Frith (1996).